Legal regulation and organisational framework of combating gambling addiction in Kazakhstan: Comparative analysis with western European models - Khamzina, Zhanna; Buribayev, Yermek (Law, State and Telecommunications Review, 2026)
[Purpose] To identify the problematic aspects of the Kazakh model of combating gambling addiction and analysing its legal and institutional foundations to determine ways to improve regulatory effectiveness. The main goal was to assess how Kazakhstan’s system of gambling regulation functions in comparison with Western European models and to identify organisational and legal challenges that impede its efficiency. [Methodology/approach/design] The research was based on a systematic approach and the comparative legal method, integrating analysis of legal acts, regulatory documents, and statistical data. The authors examined Kazakhstan’s legislative framework, institutional mechanisms of control, and organisational practices. Comparative analysis was conducted with regulatory systems of France, the UK, Denmark, and other EU states. The study also applied a structural-functional and modelling approach to propose recommendations for improving the national model of gambling regulation. [Findings] The results revealed that Kazakhstan’s model is characterised by strict state control and territorial concentration of gambling in specific areas such as the Burabai Resort Zone. The analysis demonstrated significant differences between Kazakhstan and Western European countries in terms of territorial organisation, allocation of powers, and penalty severity. The research identified major organisational problems, including a shortage of qualified personnel in supervisory bodies, lack of a unified data collection methodology, weak interagency coordination, and insufficiently developed prevention and rehabilitation programmes. [Practical implications] The findings contribute to the improvement of state policy in the field of combating gambling addiction. The study recommends introducing unified self-exclusion registers, expanding responsible gambling programmes, enhancing cross-sectoral cooperation, and developing public–private partnerships in addiction prevention. The implementation of these measures can strengthen social protection mechanisms, improve regulatory transparency, and reduce the socio-economic costs of gambling addiction in Kazakhstan. [Originality/value] This study offers a comprehensive legal and organisational analysis of Kazakhstan’s approach to gambling regulation, integrating comparative insights from Western Europe. It provides original recommendations for balancing strict state control with socially responsible practices and highlights the need for selective adaptation of international regulatory standards to national socio-economic and political conditions. The research holds particular value for policymakers, legal scholars, and public health specialists concerned with behavioural addictions and regulatory governance.